2010
DOI: 10.1136/thx.2010.151068.33
|View full text |Cite
|
Sign up to set email alerts
|

P232 The early detection of chronic obstructive pulmonary disease

Abstract: lung cancer; 2 via the general chest clinics and 1 following re-referral with persistent haemoptysis. Conclusion We have shown that almost a quarter of RALC referrals did not adhere to strict referral protocols and would have been better served by a more appropriate referral elsewhere. We are working to educate our primary and secondary care colleagues to ensure that the only appropriate cases are referred to the RALC in order to reap the maximum benefit from this resource intensive service. P231AUDIT Table 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…In contrast to general practitioners in wealthy areas, those in impoverished communities have lesser general practitioners, lesser practice nurses, a greater workload for chronic obstructive pulmonary disease, and lower economic advantages. Calderón-Larraaga et al have demonstrated this (28). There hasn't been much progress since Tudor Hart said in 1971 that the requirement for the community addressed appears to fluctuate inversely with the accessibility of effective medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to general practitioners in wealthy areas, those in impoverished communities have lesser general practitioners, lesser practice nurses, a greater workload for chronic obstructive pulmonary disease, and lower economic advantages. Calderón-Larraaga et al have demonstrated this (28). There hasn't been much progress since Tudor Hart said in 1971 that the requirement for the community addressed appears to fluctuate inversely with the accessibility of effective medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…И хотя вмешательство по отказу от курения должно быть предложено всем курящим, независимо от наличия обструктивных нарушений, пациенты с высоким риском развития ХОБЛ и уже сформировавшейся об-струкцией легкой или средней степени должны быть идентифицированы для более целенаправленных вмеша-тельств по поводу отказа от курения, ежегодных вакцина-ций от гриппа и коррекции других факторов риска ХОБЛ. Доказано, что затраты на лечение ХОБЛ легкой степени на 50% меньше, чем затраты на лечение ХОБЛ средней степени тяжести и на 90% ниже затрат на лечение тяжелой ХОБЛ [32].…”
Section: выявление бод и хбндпunclassified
“…Case studies such as the St Health primary care commissioning group have shown improved detection rates and the proportion of patients adjudged to be receiving guideline-based management has risen dramatically from 32% to 85%. Admission rates have declined by 9.2% compared with a rise of 2.3% in adjacent practices 10. Clearly caution is needed when interpreting the changes in admission rates before and after an intervention as they are prone to bias.…”
mentioning
confidence: 99%
“…As et al have demonstrated, deprived areas have fewer GPs, fewer practice nurses, a higher workload for COPD but with less financial reward than for GPs in affluent areas 10. Little change then from 1971 when Tudor Hart stated that the availability of good medical care tends to vary inversely with the need for the population served.…”
mentioning
confidence: 99%